The Movement of Indonesia’s Foreign Exchange Rates and Other Macroeconomic Variables to Its Stock Market Volatility in a Pandemic Setting - Venessa Venessa; Yulfiswandi Yulfiswandi (JURNAL ADMINISTRASI & MANAJEMEN, 2022)
This paper aims to examine the impact of foreign exchange rates on Indonesia’s composite stock index, the JKSE. To perfect the analysis, several other macroeconomic variables such as interest rates, oil prices, gold prices, as well as inflation rates were also added as proposed by preceding research. COVID-19 new infection cases were added as a moderating variable to test whether it can strengthen or weaken the correlation of each macroeconomic variable tested against the stock market. The parameter of this study is specifically focused on Indonesia to complete the lack of sufficient research conducted for the same topic and/or in the same setting. The study found all the macroeconomic variables tested in the analysis concurrently influence Indonesia’s stock market index. When each macroeconomic was tested separately, the test results found that although the direction of the impact varies, all the variables except for gold price were found to have a significant impact on the stock market in Indonesia. The moderating variable, COVID-19, was also found to have a notable influence on substantiating the impact of all the correlations tested except in moderating for exchange rates and oil price.